Media Framing and Political Image: A Case Study of Ganjar Pranowo in the U-20 World Cup Coverage on Kompas.com - Ardliansyah, Muhammad Agung; Sufyanto (CHANNEL: Jurnal Komunikasi, 2024)
This study analyzes media framing related to the cancellation of the U-20 World Cup in Indonesia, with a specific focus on Kompas.com’s coverage of Ganjar Pranowo. Using a descriptive qualitative approach, the research employs data collection techniques such as observation and documentation, applying Robert N. Entman’s framing analysis to 10 news articles published by Kompas.com.  The findings reveal that the negative framing of Ganjar Pranowo, particularly concerning his opposition to the Israeli national team’s participation, significantly impacts his political image ahead of the 2024 elections. This study highlights how media framing shapes public perception of political figures in Indonesia, underscoring the critical role that media plays in influencing political discourse and public opinion.  Future research should investigate how media framing affects other political figures and events in Indonesia to provide a broader understanding of its implications for electoral outcomes.